Interlude. Doing Research Differently? Putting Feminist Research Principles into Practice - Henri Myrttinen (Revue Internationale de Politique de Développement)
Ensuring that research is ethical and contributes to the reduction of inequalities, especially gendered, class-based and racialised power imbalances, is a central tenet of feminist research. The same, ideally, goes for peacebuilding processes. However, in spite of important and meaningful attempts to redress power imbalances, both academic research and peacebuilding work too often continue to be highly unequal endeavours. These imbalances persist between the global North and global South, but also within countries. For the most part, these imbalances are inescapable, for now at least, as both research and peacebuilding are in multiple ways entangled with broader, unequal power structures that are underpinned by patriarchy, militarism, neo-coloniality and neo-liberal capitalism. However, feminist-inspired research and peacebuilding work both do also create opportunities to analyse and question these power structures, to think and act beyond and to develop less extractive and more emancipatory alternatives and practices. This interlude examines how, as a transnational feminist research project, the researchers of this thematic volume sought to develop and foster such practices together with the communities involved in the research, and what this might mean for future research in times of the COVID-19 pandemic.